2012
DOI: 10.1007/s11904-012-0144-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Related Optimistic Beliefs and Risk of HIV Transmission: A Review of Recent Findings (2009-2012) in an Era of Treatment as Prevention

Abstract: The promising outlook for HIV treatment as prevention (TasP) offered by the recent success in clinical trials has highlighted the need for effort against over-optimism toward anti-retroviral therapy (ART). It has been of a central concern that such optimistic beliefs may fuel an increase in risk behaviors to counter the protective effect of ART on reducing overall transmissibility of HIV. The current review was conducted to provide an updated look at the potential impact of treatment-related optimistic beliefs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 26 publications
5
42
0
Order By: Relevance
“…This echoes previous research on HIV treatment optimism, which found that HIV-positive men and men who engaged in practices that put them (or their partners) at increased risk of HIV transmission were more likely to believe in the preventative benefits of ART and an undetectable viral load [7], [16], [18], [19].…”
Section: Discussionsupporting
confidence: 80%
“…This echoes previous research on HIV treatment optimism, which found that HIV-positive men and men who engaged in practices that put them (or their partners) at increased risk of HIV transmission were more likely to believe in the preventative benefits of ART and an undetectable viral load [7], [16], [18], [19].…”
Section: Discussionsupporting
confidence: 80%
“…Over the last two decades, as antiretroviral therapy has transformed HIV infection into a chronic disease, one focus of HIV prevention research has evaluated optimistic beliefs related to the availability and efficacy of antiretroviral therapy and their association with sexual risk behaviors (6-8). HIV treatment optimism has been broadly defined as favorable perceptions regarding the availability or use of antiretroviral therapy, and has traditionally been comprised of two distinct components – a belief that HIV is a less serious health threat post-infection due to the availability of antiretroviral therapy (known as ‘reduced-severity optimism’) and a belief in reduced susceptibility to HIV due to the suppressive effect of antiretroviral therapy on the viral load of infected sexual partners (known as ‘reduced-susceptibility optimism’) (9-11).…”
Section: Introductionmentioning
confidence: 99%
“…While optimism regarding the use of antiretroviral medications reflects a growing and encouraging understanding that HIV is no longer a death sentence, there is also evidence that it may lead to increased sexual risk behaviors. Previous studies of diverse populations including MSM populations in the US have found that reduced-severity and reduced-susceptibility treatment optimism were associated with HIV risk behaviors including condomless anal sex (CAS), though studies have been largely cross-sectional and therefore unable to establish a causal link (6, 12-18). …”
Section: Introductionmentioning
confidence: 99%
“…A central concern includes the potential impact of TasP and other biomedical prevention technologies on established prevention methods, such as condom use, and increases in sexual risk practices, or 'risk compensation' (Chen, 2013;Eaton & Kalichman, 2007). Some have cautioned against overly optimistic expectations, citing examples of settings with high treatment coverage, such as Australia, and the 'apparent ineffectiveness' of these 'natural TasP experiments' in reducing actual HIV incidence (Phillips et al, 2013;Smith, Powers, Muessig, Miller, & Cohen, 2012;Wilson 2012, p. 2).…”
mentioning
confidence: 99%